Study of Death of Salesman from the Perspective of Macropragmatics - Gao, Hong (Transactions on Economics, Business and Management Research, 2023)
Arthur Miller, a well-known playwright known as "the conscience of American drama", won the peak of his creative career by writing Death of a Salesman, and thus won the Pulitzer prize for drama. Death of a Salesman tells the story of how Willy Loman, a salesman, a nobody in the bottom of American society, was gradually disillusioned. Willy was also an excellent salesman with eminent business ability in his youth. At that time, he was happy and simple, and he only wanted to realize his beautiful dream. His wife, Linda, was a good housekeeper, and his two sons made him proud also. However, with time passing by, good luck was drifting away from him, and his life was gradually falling into chaos. From the perspective of macro-pragmatics, this paper analyzes the concrete application of speech act theory and conversation principle theory in Death of a Salesman to help the readers better understand and grasp the theme of the work-the disillusionment of the “American Dream ” and its practical significance: the increasing urbanization process and the rapid development of the 5G era have undoubtedly brought revolutionary influence to individuals, families and society. It has given millions of dream - seekers a much broader world to display their talents, but it may also make them be overdependent on technology and intelligence for another thing. We should recognize the situation clearly, keep up with the pace of the times, embrace new things with an open mind, and be creative "dreamers" in the new era.